Effectiveness Of Using Audio Visual MediaIn Fiqih Learning At Min 12 Pidie Jaya - Rahmiati Rahmiati; Dhiauddin Dhiauddin; Saifuddin Saifuddin (PT. Anagata Sembagi Education, 2025)
This study examines the effectiveness of using audio-visual media in teaching fiqh at MIN 12 Pidie Jaya. The learning process is an interaction that results in behavioral changes, where the role of teachers in creating a conducive learning environment is crucial. The use of modern learning media is expected to improve student understanding and create a more dynamic and interesting learning atmosphere. Although attention to this media is increasing, there are still some shortcomings in its integration with more common traditional learning methods. The method used in this study was qualitative, with data collection through observation, interviews, and document analysis. The results showed that the application of audio-visual media significantly increased student enthusiasm and made it easier to understand fiqh concepts. Students became more active and showed greater interest in the material, thus creating an interactive and enjoyable learning atmosphere. However, this study also identified several challenges, such as limited internet access, technical problems related to devices, and lack of training for teachers. These findings emphasize that although audio-visual media has great potential, these challenges need to be overcome so that fiqh learning can take place effectively. This study concludes that the integration of technology in education is an important step to prepare students for the digital era